Perceived stress among graduate students in health sciences at a military university: a mixed-method approach - Omar Mushtaq; Michael Soh; Ting Dong; Steven J. Durning; John Melton; Khalilah M. McCants; Laura Taylor; Laura Baumann; Bolanle Olapeju (BMC Medical Education)
Abstract Background There is a gap in the literature about the experiences of active-duty military students pursuing a graduate degree in health sciences at a university that emphasizes a military context. This exploratory study investigates how graduate students navigate stress in the context of a military university. Method The study applied a mixed-methods approach including a survey (N = 59) and in-depth interviews (N = 16) of students enrolled in a graduate program at the School of Medicine (368 students) and School of Nursing (187 students). Survey data was collected via email blasts to various health science departments. In the survey, students could opt-in to complete in-depth interviews. Survey data were analyzed using cross-tabulations while a transcendental phenomenological approach was employed to code and analyze qualitative data. Results Survey findings showed that more civilian students (70.6%) felt more noticeably and severely stressed than their active-duty counterparts (64.3%). Active-duty students were more likely to see their grades as a source of stress (76.2%) than their civilian counterparts (64.7%). Active-duty students were less likely to see finances as a source of stress (67.7%) than their civilian counterparts. Active-duty students were not as connected to their families and friends as their civilian counterparts were. The interviews found that active-duty students anticipated the coursework and were adept at juggling multiple demands; whereas, the civilian students centered their concerns around culture and collaboration. Active-duty students saw their program as less of a “big deal;” whereas, civilian students highlighted how they were concerned about the program and financial situations. Active-duty students relied on technical knowledge to understand their well-being; whereas, civilian students understood their well-being in holistic terms. Active-duty students focused on the idea of the individual, and how they take personal responsibility; whereas, civilian students focused more on self-care and compassion. Conclusion The study found how civilian and active-duty students experienced stress, stressors, and other aspects that contextualize their experience with stress. Study findings may inform the design of interventions to improve student well-being and resilience mechanisms among similar graduate school contexts.